MENGEMBANGKAN MINAT BACA BAGI GENERASI MUDA MELALUI KEGIATAN LITERASI BERBASIS KOMUNITAS DI DESA PASIR PUTIH, KECAMATAN NAGAWUTUNG KABUPATEN LEMBATA - Irene Alianra Rika Nahak; Bruno Rey Pantola; Eusabius Separera Niron (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
Interest in reading among the younger generation, especially in rural areas such as Pasir Putih Village, Nagawutun District, Lembata Regency is still relatively low. Although the availability of books is quite adequate, the spirit and habit of reading have not been optimally formed among students. This is due to various factors, such as the lack of mentoring, the lack of a literate environment, and the dominance of non-academic activities such as helping parents go to sea and play outside the home. To answer these challenges, students of the Independent Learning Independent Campus (MBKM) program from Widya Mandira Catholic University (Unwira) Kupang carried out socialization activities to read interests, as well as build a Village Reading Corner as a center for community-based literacy activities. The methods used include socialization and joint discussion. The results of the activity showed that there was an increase in students' awareness of the importance of reading. The Reading Corner is not only a place to read, but also a center for the growth of an open and inclusive literacy culture. This activity proves that literacy can be developed effectively through a community-based, collaborative approach and touching the social context of the village community. Students play the role of agents of change who are able to revive the spirit of learning in the midst of limitations. With continuous support from schools, village governments, and the community, this literacy movement is expected to form a young generation of villages who like to read, think critically, and are ready to face future challenges.